Assessing The Face and Content Validity of Questionnaire on the Implementation of Occupational Safety and Health Management System within 5S Certified SMEs in Malaysia - A Rhaffor, Kauthar; Jamian, Rahim; Ishak, Izuan Amin; Ismail, Mohd Fauzi (Journal of Techno-Social, 2026)
This paper presents a comprehensive study on survey instrument design, which includes face and content validity assessments for a newly developed instrument. A set of questionnaires was established as the survey instrument to gain insight into the implementation of occupational safety and health management systems (OSHMS) within 5S (sort, set in order, shine, standardize, and sustain) certified small and medium enterprises (SMEs) in Malaysia, aiming to promote safer and healthier workplaces. The questionnaire consists of 40 items organized into four main constructs: integration of OSHMS and 5S practice, planning and critical success factors, benefits of OSHMS towards SMEs performance, and action for improvement. The validity assessments were conducted through a review by a panel of experts from academia and industry. For face validity, each item underwent evaluation to confirm its alignment with the study’s objectives and received a dichotomous rating of either ‘YES’ or ‘NO’. For content validity, a four-point rating scale was employed, ranging from “not relevant” to “highly relevant” to assess how well the items reflect and represent the intended aspect being measured for a specific assessment purpose. These ratings were used to calculate the extent of agreement between raters using a percentage approach and Content Validity Index (CVI). The percentage of agreement obtained for face validity was 80%, indicating a substantial level of agreement among the expert panels, with some questions identified for revision. According to the content validity assessment, the average proportion of items judged as relevant among the six experts (S-CV1/Ave) was 0.96, meeting a satisfactory level. The validity assessments conducted have validated the items in the survey instrument, thereby indicating its readiness for distribution in a pre-test phase.